SARS-CoV-2 outbreak in a nursing home after vaccination with BNT162b2: A role for the quantification of circulating antibodies. Issue 18 (20th April 2022) - Càmara, Jordi; González-Díaz, Aida; Barrabeig, Irene; Fernández-Huerta, Miguel; Calatayud, Laura; Niubó, Jordi; Martí, Sara; Ángeles Domínguez, Mª; Ardanuy, Carmen
Abstract: We describe an outbreak of SARS-CoV-2 (B.1.351) in a nursing home. At the outbreak onset 96% of residents and 76% of HCW had received two doses of BNT162b2. Twenty-eight residents (28/53) and six HCW (6/33) were infected. Infected residents had lower levels of anti-S antibodies compared to those who were not infected (157 vs 552 U/mL). Among 50 residents with available serological status, nineteen (19/25) with serum concentration < 300 U/mL and seven (7/25) with concentration > 300 U/mL acquired SARS-CoV-2 (RR 2.7 [95 %CI 1.4–5.3]). The quantification of circulating antibodies could be useful in detecting people with an impaired immune response who are at high risk of acquiring and spreading SARS-CoV-2.